Crimes of the Pen - Emma Lieber (EJP import test, 2020)
[caption id="attachment_2341" align="aligncenter" width="526"] "Night-Goer III" by Stephen Mosblech[/caption] Summary: Hardly anyone writes about Lacan’s paper, “A Theoretical Introduction to the Functions of Psychoanalysis in Criminology.” It is one of the least commented on essays in the Ècrits, a Lacanian archive that has gone largely unarchived. Who reads this paper? Why is there no evidence of its effects? Lacan and his co-author, Michel Cénac, write that the question at issue is the relationship among revelation, truth, and efficacy, in the juridical environment and in psychoanalysis. This essay interrogates these various projects that deal in truth effects—criminal justice, psychoanalysis, speech, and writing—by way of the criminology paper and two crime texts that imbricate all of these four coordinates, Fyodor Dostoevsky’s Crime and Punishment and Henry James’s The Turn of the Screw, as a way of articulating the relationship between psychoanalysis and literature or psychoanalysis and writing.
Keywords: Criminology; Fyodor Dostoevsky; Henry James; Psychoanalysis and literature; truth